PENDAMPINGAN PENGUATAN KARAKTER SUMBER DAYA MANUSIA UNGGUL BAGI SISWA-SISWI PONDOK PESANTREN SALAFIYAH ULYA AL MUTTAQIN MADIUN JAWA TIMUR - Mirlana, Dendy Eta; Karyawati, Danik; Khoir, Septiana Nur Adila (Jurnal Abdi Masyarakat, 2023)
Building strong and positive character and self-reliance is one of the efforts in preparing and developing the younger generation or superior and advanced Human Resources. By equipping them with faith and piety, collaborated with science and technology, the younger generation or Indonesian Human Resources can become a militant generation, namely superior Human Resources, successful in the world and the hereafter. Equality Education Salafiyah Al Muttaqin Islamic Boarding School is one of the non-formal education institutions in Madiun City that organizes Wustho/junior high school and Ulya/high school education. This institution always strives to improve the quality of education gradually, measurably, and in accordance with the wishes of the community. This method of implementing community service uses participatory methods, namely through lectures, training, counseling, education which allows the service team to interact, communicate intensively, discuss and ask questions directly with the community. This activity aims to help the Equality Education Institution of the Salafiyah Al Muttaqin Islamic Boarding School in the formation of a programmed character with the hope that students who graduate from this institution will later become superior generations as the next generation of a nation who is faithful and knowledgeable, namely successful humans in this world and the hereafter.   Keywords: Building, Character, Human Resources, Excellent